The legal regulation of the crime of enforced disappearance in Iraqi law: A comparative analytical study (Raparin Journal of Humanities (RJH), 2024)
Iraq occupies an advanced position in the list of countries that suffer from widespread cases of enforced disappearance, but its penal legislation is still devoid of punishment for the crime of enforced disappearance, despite the fact that it is one of the first countries to accede to the International Convention for the Protection of All Persons from Enforced Disappearance of 2006 based on Act No. (17) of 2010 which raises the question of how criminal accountability for the perpetrators is based on national legislation, especially the Penal Code No. (111) of 1969 and the Iraqi Supreme Criminal Court Act No. (10) of 2005.To exclude the legislative shortcomings in the punitive legislation regarding the criminalization and punishment of enforced disappearance, the efforts of the Iraqi legislator in recent years have culminated in the introduction of the draft law against enforced disappearance of 2018, as well as the draft penal code of 2021, which constitutes a significant step towards Iraq’s fulfillment of its international obligations stemming from the international convention For the Protection of All Persons from Enforced Disappearance of 2006.The research is devoted to studying Penal Code No. (111) of 1969 and the Iraqi Supreme Criminal Court Act No. 10 of 2005 to examine the possibility of their application to cases of enforced disappearance. It also includes an explanation of the mechanisms for the enforcement of international conventions, especially the International Convention for the Protection of All Persons from Enforced Disappearance of 2006, in Iraqi legislation, as well as an analysis of the texts of the draft law against enforced disappearance of 2018 and the draft Penal Code of 2021 to present appropriate recommendations regarding the criminalization and punishment of enforced disappearance in them.